ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN E-COMMERCE BAGI PELAKU USAHA MIKRO KECIL MENENGAH (FOOD AND BEVERAGES) DI KECAMATAN TAMBAKSARI KOTA SURABAYA - Rosmanda, Rafensa; Mubarokah, Mubarokah; Indah, Pawana Nur (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aims to analyze e-commerce adoption among Small and Medium Enterprises (SMEs) in the Food and Beverage sector in Tambaksari Sub-district, Surabaya City. Using questionnaires for data collection and Structural Equation Modeling for data analysis, this study involved a sample of 80 respondents from the SME population in the area. Analysis of the demographics and business characteristics of the respondents showed that most respondents were female, aged between 41-50 years, with the highest level of education being high school or vocational school. The study used path diagrams to illustrate the relationship between variables and conducted convergent validity, discriminant validity, and composite reliability tests to validate the model. The results of hypothesis testing show a significant relationship between perceived usefulness, ease of use, behavioral attitudes, subjective norms, and behavioral control factors with e-commerce usage. These findings underscore the importance of e-commerce adoption in the business development strategy of SMEs in the Food and Beverage sector in Tambaksari Sub-district, Surabaya.